[Lava at Fish Plant in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of lava rock at a fish processing plant. The white plant buildings sits in the background, split between two sections with a central bridge-like section connecting it. Large, pink, Icelandic text sits along the side of the bridge structure. The dark lava rock sits in a pile to the right behind the building. A red truck moves through the bridge section toward the harbor where many white boats sit. Two people walk along the dark, dirt road to the left.